2018
DOI: 10.1021/acs.jcim.8b00054
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Regression for Quantitative Structure–Activity Relationship Modeling—Quantifying Prediction Uncertainty

Abstract: Making predictions with an associated confidence is highly desirable as it facilitates decision making and resource prioritization. Conformal regression is a machine learning framework that allows the user to define the required confidence and delivers predictions that are guaranteed to be correct to the selected extent. In this study, we apply conformal regression to model molecular properties and bioactivity values and investigate different ways to scale the resultant prediction intervals to create as effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 54 publications
(103 reference statements)
3
79
0
Order By: Relevance
“…To improve reliability of the models, the chemical space was considered by including information about the nearest neighbours to normalise the conformal predictions. While such a normalisation of the nc scores is important for regression models [56,57], to the best of our knowledge, it has not been applied to classification tasks so far. Including the KNN normalisation clearly improved validity for internal validation and the in-house dataset from 0.81 to 0.85 and from 0.59 to 0.82 at 0.2 SL, respectively (see Additional file 1: Table S2).…”
Section: Conformal Predictors-validation Of Aa Modelmentioning
confidence: 99%
“…To improve reliability of the models, the chemical space was considered by including information about the nearest neighbours to normalise the conformal predictions. While such a normalisation of the nc scores is important for regression models [56,57], to the best of our knowledge, it has not been applied to classification tasks so far. Including the KNN normalisation clearly improved validity for internal validation and the in-house dataset from 0.81 to 0.85 and from 0.59 to 0.82 at 0.2 SL, respectively (see Additional file 1: Table S2).…”
Section: Conformal Predictors-validation Of Aa Modelmentioning
confidence: 99%
“…Each QSAR model was validated using both internal (i.e., cross-validated) and external (i.e., test set) error measures and only models that satisfied stringent quality criteria were used for the construction of the rv-QAFFP fingerprint. The applicability domain of individual QSAR models was estimated using inductive conformal prediction [54][55][56][57]. The rv-QAFFP fingerprint is composed of 440 affinities predicted for the panel of assays covering 376 distinct molecular targets models, further referred to as point prediction models, out of the initial set of 1360 models were considered to be reliable and were used for the construction of the rv-QAFFP fingerprint (Additional file 1).…”
Section: Rv-qaffp Fingerprint Constructionmentioning
confidence: 99%
“…Throughout this work we considered a Confidence Level of 80% unless otherwise stated, as this confidence level in our experience represents a generally suitable trade-off between efficiency and validity 39 .…”
Section: Conformal Prediction -Dropout Conformal Predictionmentioning
confidence: 99%
“…revealed that the exponential scaling improves the efficiency of Conformal Predictors built on bioactivity data sets39 . This scaling sets the upper value for the list of nonconformity values to be equal to the largest residual in the validation set, as the exponential converts low 0 values to values close to unity.…”
mentioning
confidence: 99%
See 1 more Smart Citation